INHIBITORY EFFECT OF ONION (ALLIUM CEPA LINN) AND SUGAR PASTE MIXTURE ON STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI BY IN VITRO - Tahiruddin Tahiruddin; Diah Indriastuti (YCAB Publisher, 2019)
Background: Staphylococcus aureus and Escherichia coli are infection agents. The onion is known to have antibacterial properties. Meanwhile, sugar paste is effective to inhibit bacterial growth. Objective: This study aimed to identify the antibacterial activity of onion extract (Allium cepa Linn) and sugar paste mixture on staphylococcus aureus and Escherichia coli by in vitro. Methods: We used a post-test-only control group design with a completely random design. The onion extract with sugar paste mixture was divided into 4 concentrations; 25%, 50%, 75% and 100% with 3 repetitions. The data were analyzed by measuring inhibition zone diameter and tested using the One-Way Analysis of Variance (ANOVA) and Tukey test. Results: Findings showed that on average, the antibacterial activity of onion extract and sugar paste mixture on staphylococcus aureus was 14.57mm, 17.44mm, 18.36mm, and 22.28mm, respectively 25%, 50%, 75%, and 100% concentrations. Meanwhile, on Escherichia coli, it was 17.27mm, 19.67mm, 20.31mm, and 21.62mm. Conclusion: onion extract and sugar paste mixture can inhibit the growth of Staphylococcus aureus and Escherichia coli.